Autologous chondrocyte implantation (ACI) for cartilage defects of the knee: a guideline by the working group “Clinical Tissue Regeneration” of the German Society of Orthopaedics and Trauma (DGOU) - Niemeyer, Philipp; Richter, Wiltrud (The knee, 2016)
Background: Autologous chondrocyte implantation (ACI) is an established and well-accepted procedure for the treatment of localised full-thickness cartilage defects of the knee. Methods: The present review of the working group “Clinical Tissue Regeneration” of the German Society of Orthopaedics and Trauma (DGOU) describes the biology and function of healthy articular cartilage, the present state of knowledge concerning therapeutic consequences of primary cartilage lesions and the suitable indication for ACI. Results: Based on best available scientific evidence, an indication for ACI is given for symptomatic cartilage defects starting from defect sizes of more than three to four square centimetres; in the case of young and active sports patients at 2.5cm2, while advanced degenerative joint disease needs to be considered as the most important contraindication. Conclusion: The present review gives a concise overview on important scientific background and the results of clinical studies and discusses the advantages and disadvantages of ACI. Level of Evidence: Non-systematic Review
Gesehen am 12.03.2019